Integrating Local Tourism Potential into Environmental Education: A Case Study of Toya Village - Musyaddad Akbar; Badarudin Badarudin; Muh Fahrurrozi (JMET: Journal of Management Entrepreneurship and Tourism, 2026)
This study examines how local tourism potential can be integrated into environmental education as a contextual and experiential learning resource for strengthening environmental literacy and pro-environmental behavior. Using a qualitative case study design, the research was conducted in Toya Village, Indonesia, a rural tourism destination characterized by ecological diversity, natural landscapes, community-based tourism practices, and socio-cultural resources. Data were collected through field observations, semi-structured interviews, document analysis, and focus group discussions involving tourism stakeholders, educators, students, village representatives, and community members. The findings show that local tourism assets, including natural ecosystems, biodiversity, local wisdom, traditional agricultural practices, and community-based tourism activities, can be transformed into meaningful environmental learning resources. These resources support place-based and experiential learning by enhancing environmental knowledge, awareness, critical thinking, environmental values, and participation in conservation-oriented activities. The study contributes to the literature by bridging environmental education and sustainable tourism, an area that remains underdeveloped in formal education frameworks, particularly in rural and developing-country contexts. It proposes a conceptual linkage between local tourism potential, environmental learning processes, learning outcomes, and pro-environmental behavioral change. The findings imply that curriculum integration, teacher capacity building, community participation, and cross-sector collaboration are essential for optimizing tourism destinations as sustainable learning environments.